TRAINING PROFESSIONAL COMPETENCES OF LEGAL TEXT TRANSLATORS IN THE FRAMEWORK OF POSTGRADUATE STUDIES - SEKUŁA, Justyna (Comparative Legilinguistics, 2016)
The article presents the results of a comparative analysis of postgraduate studies in terms of training professional competences of the legal text translators, which are organized by the University of Warsaw, UNESCO – Chair for Translation Studies and Intercultural Communication of the Jagiellonian University, Adam Mickiewicz University in Poznań, the University of Wrocław as well as Nicolaus Copernicus University in Toruń. It includes a comparison of range of education within the above-mentioned studies and determines the usefulness of professional development in the form of the postgraduate studies in the later work experience.